2015
DOI: 10.1088/1748-3190/10/5/056004
|View full text |Cite
|
Sign up to set email alerts
|

Error analysis and assessment of unsteady forces acting on a flapping wing micro air vehicle: free flight versus wind-tunnel experimental methods

Abstract: An accurate knowledge of the unsteady aerodynamic forces acting on a bio-inspired, flapping-wing micro air vehicle (FWMAV) is crucial in the design development and optimization cycle. Two different types of experimental approaches are often used: determination of forces from position data obtained from external optical tracking during free flight, or direct measurements of forces by attaching the FWMAV to a force transducer in a wind-tunnel. This study compares the quality of the forces obtained from both meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…approximately 70Hz. As a comparison, previous work on a similar test platform showed that 200Hz-sampled optical tracking data only resulted in reliable information up to 32Hz in the accelerations obtained from double differentiation [16]. The high resolution attained is relevant not only for the forces and moments, but also for the states themselves, and especially the body velocities, which cannot be estimated as effectively by either IMU or optical tracking alone.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…approximately 70Hz. As a comparison, previous work on a similar test platform showed that 200Hz-sampled optical tracking data only resulted in reliable information up to 32Hz in the accelerations obtained from double differentiation [16]. The high resolution attained is relevant not only for the forces and moments, but also for the states themselves, and especially the body velocities, which cannot be estimated as effectively by either IMU or optical tracking alone.…”
Section: Introductionmentioning
confidence: 78%
“…While sampling up to 1024Hz is possible, internal low-pass filtering at 256Hz implies that such sampling frequencies would not yield accurate additional information, and it was also found that at higher rates, significant numbers of frames were being lost, presumably as a result of CPU overloading. Moreover, previous work with similar ornithopters showed that very high-frequency content becomes increasingly difficult to distinguish from noise [16].…”
Section: Experimental Setup a Test Vehiclementioning
confidence: 99%
See 3 more Smart Citations